PENERAPAN HUKUM PIDANA PADA KASUS PELANGGARAN LALU LINTAS YANG MENYEBABKAN KORBAN MENINGGAL DUNIA(Studi Pada Putusan Nomor 153/Pid.Sus/2015/PN.Sda) - Gerik Kaniago Pratama; Samuji (INTELIGENSIA MEDIA, 2023)
Cases of traffic violations that resulted in the death toll have become a serious concern in the criminal legal system. This article focuses on the application of criminal law in the context, with a special analysis of the decision number 153/Pid.Sus/2015/PN.Sda. This study aims to explore and analyze the legal aspects involved in this case, as well as the impact of legal decisions on the enforcement of justice. The research method used is a normative approach to legal decisions that are relevant to the topic. Data were analyzed by considering the legal view, the argument used in the trial, as well as the legal basis underlying the judge's decision. The results of the analysis highlighted the role of criminal law in handling cases of traffic accidents resulting in death. In addition, the conclusion of this study discusses the implications of the decision on efforts to maintain justice in the legal system, as well as the potential improvement or change that can be applied in law enforcement related to similar cases in the future. In conclusion, this article provides in depth insights on the application of criminal law in the context of traffic violation cases that lead to fatal accidents, by analyzing the case study of decision number 153/Pid.Sus/2015/PN.Sda. The practical implications of this study highlighted the importance of fair and fair law enforcement in handling similar cases.